Acceptability of using point-of-care tests for cancer in primary care: a UK public mixed-methods study - Ayaz-Shah, Anam A.; Neal, Richard D.; Haider, Zainab F.; Lloyd, Kelly E.; Green, Sophie M. C.; Nasir, Nayab; Thompson, Mathew J.; Smith, Samuel G. (Frontiers in Cancer Control and Society, 2025)
IntroductionPoint-of-care tests (POCTs) for cancer in primary care have the potential to increase diagnostic certainty, improve triage and enhance patients' experience of diagnosis. However, there is limited evidence to support their adoption, and patient preferences have not previously been investigated. This study aimed to assess the prospective acceptability of POCTs for cancer in primary care based on a hypothetical vignette.MethodsThis was a mixed-methods study based on the Theoretical Framework of Acceptability (TFA) consisting of a quantitative online survey and remote qualitative interviews with the UK public. Quantitative data were reported as frequencies. Qualitative data were analyzed combining inductive and deductive framework analysis.ResultsTwo thousand three hundred three adults completed the online survey, and 27 participants were recruited for follow-up interviews. The survey indicated most (92%, 2,116/2,303) participants found the potential use of POCTs for cancer acceptable or very acceptable. There were some small demographic differences in levels of acceptability. Interview findings indicated acceptability was primarily driven by a quick turnaround time for test results, with a preference for testing even when results were indicative and not confirmatory. Participants highlighted the importance of test accuracy, clear communication regarding test limitations, and having a genuine choice in the decision to take the test. Participants also discussed the improved likelihood of adherence to referrals for invasive testing following a positive POCT.DiscussionThe use of POCTs for cancer in primary care is acceptable to the UK public, however important considerations regarding test accuracy and consenting for tests should be considered prior to implementation. Future adoption should evaluate acceptability of specific cancer POCTs, particularly in underserved populations.